Convenient, rapid and economic detection and semi-quantification of American cockroach allergen in the environment - Anchalee Tungtrongchitr (2018)
Background: Measuring allergen levels in the environment provides useful information to guide the management of allergic patients. A laboratory-based test kit sandwich ELISA for quantification of Per a 9, the major allergen of Periplaneta americana was recently developed. However, it is not suitable for screening. Objective: To develop a simple, rapid, and economic format for semi-quantification of Per a 9 assay using dot-blot ELISA technique. Methods: The efficacy of direct dot-blot ELISA and sandwich dot-blot ELISA was evaluated. Direct dot-blot ELISA was selected for further modification into 6 protocols. The selected protocol of direct dot-blot was further compared with the laboratory-based test kit, sandwich ELISA. Results: The lowest detection limits in protocols no. 1-6 were 3.9, 15.6, 15.6, 62.5, 125 and 62.5 μg/ml of native Per a 9 whereas time required for each protocol was 145, 45, 30, 26, 18 and 26 minutes, respectively. The sensitivity of direct dot-ELISA was 3.9 μg/ml of Per a 9. Protocol no. 3 was the most suitable assay because its detection limits were as low as 15.6 μg/ml of CR allergen and the total process took only 30 minutes. In comparison with the 2 days required for laboratory sandwich ELISA, the selected protocol provided a similar yield of allergen detection but it offers significant savings of time. Additionally, this method could be easily interpreted by various groups of people. Conclusion: This modified direct dot-blot ELISA is the first membrane ELISA which is a semi-quantitative test appropriate for screening American cockroach allergen owing to its simplicity, speed and good yield.